Silverlight 4 in action - Brown, Pete (Manning, 2010)
Anyone who has gotten a taste of what it can do knows that Silverlight represents an entirely new level of rich web interface technology for Microsoft developers. With Silverlight, developers can use JavaScript, C#, and other languages to build user-friendly, interactive, and visually-dazzling web applications that work in most major browsers. Silverlight 4 in Action is a comprehensive guide to Silverlight, taking you from Hello World through the techniques you'll need to build sophisticated rich web apps. This new edition covers all the new features added in the latest versions of Silverlight, Visual Studio, and Expression Blend, along with the best practices emerging in the Silverlight community. With more than 50% new content, you'll take a mind-expanding trip through the technology, features, and techniques required to build applications ranging from media, to custom experiences, to business applications to games. Beyond the fundamentals, you'll find numerous practical examples of important patterns like the ViewModel (or MVVM) pattern, and effective practices for developing real-world applications. You'll delve into the underlying object model and what makes Silverlight tick. Business application developers will appreciate the coverage of the exciting new.NET RIA Services. Combined with advanced binding and validation techniques, they help you visualize how to make your application development super productive and your architecture flexible enough to implement solutions in any problem domain. Silverlight 4 in Action devotes extensive coverage to flexible layout components, the extensible control model, the communication framework, and the data-binding features-all cornerstones of software development. You'll master Silverlight's rich media and vivid graphical and animation features. The closing chapters include a variety of Silverlight deployment and customization scenarios. Finally, Silverlight 4 in Action doesn't leave you in the dark when it comes to testing and debugging your applications. Techniques, tools, and patterns to support testable Silverlight applications are woven throughout the chapters, with additional dedicated content on the specifics of testing and debugging in Silverlight.
Print version record
Keywords: Silverlight (Electronic resource); Multimedia systems; Web sites -- Design; Application software -- Development; Multimédia; Sites Web; Conception; Logiciels d'application; Développement; Web sites; Design; Application software; Development